2005
DOI: 10.2193/0022-541x(2005)069[0498:etohim]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Tests of Hunter–covey Interface Models

Abstract: Quail hunting consists of a complex set of behaviors that involve humans, pointing dogs, and wild birds. The recent development of models known as Hunter-Covey Interface (HCI) theory provides an opportunity to analyze how we perceive, understand, and manage quail hunting. There are 2 groups of HCI models: static and dynamic. The static HCI model predicts daily hunting mortality based on the velocity of the hunt and area covered during a hunt. The dynamic HCI models estimate the probability of flushing a covey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…We We collected all locations in the track file at 7-second intervals. Hardin et al (2005) showed the 7-second interval was favorable for 2 reasons. First, the interval allowed the GPS units to record data continuously for about 4 hours, which allowed all information from a hunt to be collected on one unit.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…We We collected all locations in the track file at 7-second intervals. Hardin et al (2005) showed the 7-second interval was favorable for 2 reasons. First, the interval allowed the GPS units to record data continuously for about 4 hours, which allowed all information from a hunt to be collected on one unit.…”
Section: Methodsmentioning
confidence: 97%
“…Second, turning angles of dogs showed little difference between the 7-second interval and longer intervals. Therefore, the 7-second interval optimized data collection for each hunt (Hardin et al 2005). We converted GPS tracks to Universal Transverse Mercator coordinates and downloaded to a spreadsheet using Department of Natural Resources Garmin 5.1.1 software (Minnesota Department of Natural Resources, St. Paul, MN).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Provision of supplementary food in feeders or food plots may increase winter survival if bobwhites are better able to cope with inclement weather with additional food or body reserves Kemp 1997, Doerr andSilvy 2006). However, potential benefits of improved cover and supplemental feeding could be negated by higher mortality rates if hunters or natural predators concentrate their effort near food plots or habitats preferred by bobwhites (Roseberry 1979, Williams et al 2000, Madison et al 2002, Haines et al 2004, Hardin et al 2005). Exposure to harvest may also increase natural mortality if bobwhites incur greater predation risk after disturbance by hunters or during movements from small to larger coveys (Curtis et al 1988, Williams et al 2003b.…”
Section: Sensitivity Of Demographic Parametersmentioning
confidence: 99%